Identification of Dominant Risks in Public-Private Partnership (PPP) Projects in the Health Sector - Hana Trisnadewi; Farida Rachmawati (LPPM Institut Pendidikan Nusantara Global, 2026)
Public-Private Partnership (PPP) projects in the health sector have high complexity with various risks that can hinder project success. This study aims to identify the most relevant and significant risks in health sector PPP projects. The research method uses a quantitative approach with questionnaire surveys to four experts consisting of representatives from government and business entities experienced in hospital PPP projects. Data were analyzed using the Probability Impact Matrix (PIM) to determine risk significance levels based on probability of occurrence and impact. The results show eight dominant risks in high and very high categories. Very high category risks include JKN/Availability Payment and delays in JKN claim payments. High category risks include regional fiscal sustainability, shortage of healthy human resources, land risks, regulatory uncertainty, construction delays, and construction cost increases. These findings indicate that operational risks dominate health sector PPP projects, with high dependence on national health policies and local government fiscal capacity. This research provides practical contributions for stakeholders in designing more effective risk mitigation strategies for health sector PPP projects.